Seroprevalence and Risk Factors for Bovine Coronavirus Infection among Dairy Cattle and Water Buffalo in Campania Region, Southern Italy - Gianmarco Ferrara; Valentina Iovane; Elvira Improda; Giuseppe Iovane; Ugo Pagnini; Serena Montagnaro (Animals, 2023)
Cattle and water buffalo are the main livestock species that are raised in the Campania region, southern Italy, and they contribute significantly to the regional rural economy. Currently there are limited data on the prevalence of relevant impact infections, such as bovine coronavirus (BCov), an RNA virus that causes acute enteric and respiratory disease. Although these diseases are described primarily in cattle, there have been reports of spillovers to other ruminants, including water buffalo. Here, we determined the seroprevalence of BCoV in cattle and water buffalo in the Campania region of southern Italy. An overall seroprevalence of 30.8% was determined after testing 720 sampled animals with a commercial enzyme-linked immunosorbent assay. A risk factor analysis revealed that the seropositivity rates in cattle (49.2%) were higher than in water buffalo (5.3%). In addition, higher seroprevalence rates were observed in older and purchased animals. In cattle, housing type and location were not associated with higher seroprevalence. The presence of BCoV antibodies in water buffalo was associated with the practice of co-inhabiting with cattle, demonstrating that this practice is incorrect and promotes the transmission of pathogens between different species. Our study found a considerable seroprevalence, which is consistent with previous research from other countries. Our results provide information on the widespread distribution of this pathogen as well as the risk factors that are involved in its transmission. This information could be useful in the control and surveillance of this infection.